Odorant Normative Data for Use in Olfactory Memory Experiments: Dimension Selection and Analysis of Individual Differences - Moss, Andrew G.; Miles, Christopher; Elsley, Jane V.; Johnson, Andrew J. (Frontiers in Psychology, 2016)
The present study reports normative ratings for 200 food and non-food odors. One hundred participants rated odors across measures of verbalisability, perceived descriptive ability, context availability, pleasantness, irritability, intensity, familiarity, frequency, age of acquisition, and complexity. Analysis of the agreement between raters revealed that four dimensions, those of familiarity, intensity, pleasantness, and irritability, have the strongest utility as normative data. The ratings for the remaining dimensions exhibited reduced discriminability across the odor set and should therefore be used with caution. Indeed, these dimensions showed a larger difference between individuals in the ratings of the odors. Familiarity was shown to be related to pleasantness, and a non-linear relationship between pleasantness and intensity was observed which reflects greater intensity for odors that elicit a strong hedonic response. The suitability of these data for use in future olfactory study is considered, and effective implementation of the data for controlling stimuli is discussed.